THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE CREATIVITY MEDIATED BY PSYCHOLOGICAL EMPOWERMENT - Simamora, Idham Kurnia (FIA UB, 2021)
This study aimed to determine the influence of transformational leadership on employee creativity through the psychological empowerment of employees as a mediating variable. This research is categorized as an explanatory research. The respondents of this study were permanent employees of PT. Bank Rakyat Indonesia Tbk (Persero), Branch Malang Kawi, East Java amounting to 80 people. The analytical method used is path analysis. The results demonstrated that transformational leadership has a direct influence on employee creativity, positively and significantly. Transformational leadership also has an indirect influence on employee creativity through the psychological empowerment of employees. In addition, transformational leadership has a positive and significant influence on the psychological empowerment of employees, and psychological empowerment itself has a positive and significant effect on employee creativity.